Noonan Syndrome Case Report: PTPN11 and Other Potential Genetic Factors Contributing to Lethal Hypertrophic Right Ventricular Cardiomyopathy. (July 2019) - Daoud, Elena; Zwick, David
Noonan syndrome is a genetic condition with a heterogeneous phenotype and multisystem involvement. The pathogenesis of this disorder has been attributed to the mutations in the RAS/MAPK signaling pathway involved in cell proliferation and differentiation. The most common clinical presentations are related to cardiovascular abnormalities with congestive heart failure as the most common mechanism of death. We present the autopsy findings from a Noonan syndrome patient who died as a result of an unusual form of right ventricular obstruction associated with a rare PTPN11 variant previously reported without details of the cardiac findings. Discussion follows that includes overview of the incidence, genetic causes, types of right-sided obstructive lesions, PTPN11 genotype—cardiac phenotype correlations, and other potential mechanisms that may contribute to disease heterogeneity.